Cord Blood-Derived Stem Cells Suppress Fibrosis and May Prevent Malignant Progression in Recessive Dystrophic Epidermolysis Bullosa. (24th September 2018) - Liao, Yanling; Ivanova, Larisa; Zhu, Hongwen; Plumer, Trevor; Hamby, Carl; Mehta, Brinda; Gevertz, Annie; Christiano, Angela M.; McGrath, John A.; Cairo, Mitchell S.
Abstract : Recessive dystrophic epidermolysis bullosa (RDEB) is a severe skin fragility disorder caused by mutations in the Col7a1 gene. Patients with RDEB suffer from recurrent erosions in skin and mucous membranes and have a high risk for developing cutaneous squamous cell carcinoma (cSCCs). TGFβ signaling has been associated with fibrosis and malignancy in RDEB. In this study, the activation of TGFβ signaling was demonstrated in col7a1 −/− mice as early as a week after birth starting in the interdigital folds of the paws, accompanied by increased deposition of collagen fibrils and elevated dermal expression of matrix metalloproteinase (MMP)-9 and MMP-13. Furthermore, human cord blood-derived unrestricted somatic stem cells (USSCs) that we previously demonstrated to significantly improve wound healing and prolong the survival of col7a1 −/− mice showed the ability to suppress TGFβ signaling and MMP-9 and MMP-13 expression meanwhile upregulating anti-fibrotic TGFβ3 and decorin. In parallel, we cocultured USSCs in a transwell with RDEB patient-derived fibroblasts, keratinocytes, and cSCC, respectively. The patient-derived cells were constitutively active for STAT, but not TGFβ signaling. Moreover, the levels of MMP-9 and MMP-13 were significantly elevated in the patient derived-keratinocytes and cSCCs. Although USSC coculture did not inhibit STAT signaling, it significantly suppressed the secretion of MMP-9 and MMP-13, and interferon (IFN)-γ from RDEB patient-derived cells. Since epithelial expression of these MMPs is a biomarker of malignant transformation and correlates with the degree of tumor invasion, these results suggest a potential role for USSCs in mitigating epithelial malignancy, in addition to their anti-inflammatory and anti-fibrotic functions. Abstract : This study demonstrates the dual effects of USSCs on modulating RDEB skin microenvironment. USSCs exert anti-fibrotic function by suppressing phosphorylation of Smad2/3 in the fibroblasts (Fb) and macrophages (MΦ) of the skin, inhibiting MMP-9 and MMP-13 dermal expression and upregulating anti-fibrotic TGFβ3 and DCN expression. USSCs also attenuate secretion of MMP-9 and MMP-13, which correlate with epithelial malignant transformation, from keratinocytes (Kc) and cSCCs derived from patients with RDEB.